IL-17RB enhances thyroid cancer cell invasion and metastasis via ERK1/2 pathway-mediated MMP-9 expression. (October 2017) - Ren, Lei; Xu, Yapei; Liu, Cong; Wang, Shoujun; Qin, Guijun
Highlights: IL-17RB expression is upregulated in both thyroid cancer cells and tissues. Activation of IL-17RB by IL–17B promote thyroid cancer cell invasion, growth and migration in vitro . IL-17RB enhances thyroid cancer cell metastasis and growth in vivo. . IL-17RB induces ERK1/2 activation and increases MMP-9 expression in vitro and in vivo . Abstract: IL-17RB, a member of the IL-17 receptor family that can be activated by IL-17B, has been proved to be involved in inflammatory diseases and cancers. However, the function of IL-17RB in thyroid cancer is still unknown. In this study, IL-17RB expression in thyroid cancer cell lines and tissues was examined by real-time PCR and western blot. The effects of IL-17RB on cell invasion and migration were determined by in vitro invasion and migration assays, while the effects of IL-17RB on cell metastasis were analyzed by in vivo experiments. The results showed that IL-17RB expression was upregulated in both thyroid cancer cells and tissues. IL–17B dose-dependently promoted the invasion, growth and migration of thyroid cancer cells, whereas knockdown of IL-17RB attenuated the effects of IL–17B in vitro . Moreover, IL-17RB was involved in the metastasis and growth of thyroid cancer cells in vivo . In addition, IL-17RB induced ERK1/2 activation and increased MMP-9 expression in vitro and in vivo . Inhibition of ERK1/2 pathway blocked the IL-17RB-mediated thyroid cancer cell invasion and MMP-9 expression. Together, our findings demonstrate that IL-17RB can enhance thyroid cancer cell invasion and metastasis via ERK1/2 pathway-mediated MMP-9 expression, suggesting that IL-17RB may act as a potential therapeutic target for thyroid cancer therapy.